Pendidikan Karakter dalam Pembelajaran PAI di Sekolah Dasar: Peran Guru sebagai Teladan - Ahmad Yani (CV Edu Tech Jaya, 2024)
Character education has a very important role in shaping students' personalities, especially at the elementary school level. Islamic Religious Education (PAI) as one of the subjects taught in elementary schools has great potential in developing students' characters. Teachers as educators have a very important role, not only in transferring knowledge, but also in being role models for students. This study aims to analyze the role of PAI teachers in character education in elementary schools and how teachers act as role models for students. This study uses a qualitative approach with a case study method. Data were collected through interviews with PAI teachers, learning observations, and documentation. The results of the study showed that PAI teachers act as role models in implementing character values ​​such as honesty, discipline, tolerance, and compassion. This role is very important in fostering character values ​​that can be applied by students in everyday life. Teachers who demonstrate good and consistent behavior can have a significant influence on the development of students' character.